Legal Protection of Workers in Time Work Agreements in Indonesia - Putri, Shanty Hermalia; Adil Lbs, Muhammad Hafizh; Soliha, Ulfa Safira (AMK : Abdi Masyarakat UIKA, 2023)
Currently, there have been violations in the implementation of the Specific Time Work Agreement (PKWT) system. The Fixed Term Work Agreement (PKWT) that was implemented was not in accordance with or did not even refer to the PKWT rules regulated in Law Number 13 of 2003 concerning Employment. There are still many companies that implement PKWT that do not comply with the provisions stipulated in work agreements and the Employment Law, so they require legal certainty and provide protection for all parties. The discussion in this research is: 1. How certain time work agreements are regulated in Indonesia. 2. What is the legal protection for contract workers in fixed-term work agreements in Indonesia.